Familial Mediterranean Fever as a Cause of Recurrent Pleurisy in a Child With Crohn’s Disease: A Case Report - Ola Alhalabi; Khaled Abouhazima; Fatima Al Maadid; Ahmed Abushahin (Case Reports in Pulmonology)
Conclusions: FMF should be considered for children with CD who exhibit pulmonary symptoms that do not respond to CD treatment.